Online service "sportreserve" as an effective resource for monitoring the physical fitness of students - Fursov, A.V.; Sinyavsky, N.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the functionality of the online service of the automated information system (AIS) "Sportreserve" in working with the sports reserve, selection and support of the most gifted children at the stages of sports training. Methods and structure of the study. The tools for developing a software service were defined as the most universal cross-platform PHP Storm IDE solutions designed for writing interface programming text and implementing a database management system. More than 50,000 students from budgetary educational institutions of the city of Surgut were involved in testing the online service of the AIS "Sportreserve". Results and conclusions. The AIS "Sportreserve" has automated the main algorithms, as well as created directories for recording the data of students passing the standards of the GTO complex at all stages of sports training with uploading an individual electronic passport of an athlete and relevant analytical data. The program provides the following functions: automated recording of data on sports activities of athletes; generation of individual reports, creation of databases by sections of the athlete's digital passport.